BIMBINGAN TEKNIS PEMBUATAN PUPUK CAIR DI DESA BINAAN POLINEMA, WRINGINSONGO – TUMPANG - Sigit Hadiantoro; Hardjono Hardjono; Ade Sonya Suryandari; Noor Isnaini Azkiya (P3M Politeknik Negeri Malang, 2023)
Wringinsongo Village, Tumpang is an area that has enormous natural resource potential. The main livelihoods of the residents of Wringinsongo Village are farmers, working on plantations and also raising livestock. These three livelihoods produce various wastes that can be used as materials for making liquid fertilizer. Liquid fertilizer is a solution from the decay of organic materials derived from plant residues, animal waste, which contains more than one nutrient element. The best raw materials for liquid fertilizer are wet organic matter or organic materials that have a high water content, such as fruit and vegetable residues. This PPM program aims to help the assisted villagers in solving their problems by providing training on the manufacture of liquid fertilizer to utilize and reduce household waste in the assisted villages. The methods used in PPM activities are counseling, training and monitoring. The results of the PPM activity showed an increase in participants' knowledge and skills in making liquid fertilizer. Furthermore, several PPM achievements that have been achieved include: Articles published in national journals with ISSN, and publication of activities on social media.